Implementation of Green Marketing in Digital Marketing Management - Muhamad Agung Dharmajaya; Eva Sutihat; Diba Anggraini Aris (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
The development of digital technology is encouraging companies to adopt marketing strategies that are not solely profit-oriented but also consider environmental sustainability. One emerging approach is green marketing, integrated into digital marketing management. This study aims to analyze the implementation of green marketing in digital marketing management and identify strategies, challenges, and their impact on brand image and consumer trust. The research method used was a qualitative approach with descriptive methods. The results show that the implementation of green marketing in digital marketing management has a positive impact on brand image formation and increased consumer trust. The implementation of a digital marketing strategy that integrates environmentally friendly products, sustainable pricing, green distribution, and educational content-based promotions can increase consumer awareness of the value of sustainability. However, the effectiveness of green marketing implementation is still affected by several obstacles, such as high costs, the risk of greenwashing, and differences in consumer awareness of environmental issues. Therefore, a consistent, transparent, and integrated strategy is needed for optimal implementation of green marketing in digital marketing.